Efficacy of Ficus tikoua Bur. extract in ethylene glycol-induced urolithiasis model in SD rats - Bervinova, Arina V.; Palikov, Viktor A.; Mikhailov, Evgeny S.; Palikova, Yulia A.; Borozdina, Natalya A.; Kazakov, Vitaly A.; Rudenko, Pavel A.; Tukhovskaya, Elena A.; Dyachenko, Igor A.; Slashcheva, Gulsara A.; Goryacheva, Natalya A.; Sadovnikova, Elena S.; et al. (Frontiers in Pharmacology, 2022)
The development of new herbal preparations for the treatment of urolithiasis is an urgent task of medical science. Ficus have attracted the attention of pharmacologists due to a wide range of biological properties, including antioxidant, anti-inflammatory, antibacterial and antifungal activity. We studied the effectiveness of Ficus tikoua Bur. in SD rats in which urolithiasis was induced by 6 weeks of oral administration of ethylene glycol 0.5% ad libitum instead of drinking water. Administration of the extract of Ficus tikoua Bur., as well as comparative drug Cystone® after modeling of urolithiasis lead to the restoration of diuresis and the concentration of inorganic phosphates starting from the 6th week of the experiment. The use of the Ficus tikoua Bur. extract for 6 weeks, both during the modeling of urolithiasis and during the recovery period, led to the restoration of the percentage of lymphocytes in the blood, content of sodium, chlorine and inorganic phosphates in the blood to the control level. Thus, the extract of Ficus tikoua Bur. seems to be a promising drug for effective treatment of the initial stages of the development of urolithiasis.